Pengaruh Fixed Asset Turnover Ratio (Fato) dan Debt to Assets Ratio (Dar) terhadap Return on Assets (Roa) pada PT Astra Internasional Tbk Periode 2014-2023 - Chika Dyah Kurniadi; Mohamad Safii (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This research aims to examine the impact of the Fixed Asset Turnover Ratio and the Debt to Asset Ratio on the Return On Assets of PT Astra International Tbk over the period 2014-2023. The study adopts a descriptive quantitative method, utilizing several statistical tools including Classical Assumption Test (Normality, Multicolinearity, Heterocedasticity, and Autocorrelation), the coefficient of determination, multiple linear regression, and hypothesis testing (t-test and F-test). The findings reveal that the Fixed Asset Turnover Ratio has a positive and statistically significant effect on Return On Asset, supported by a t-value of 4,549, which exceeds the t-table value of 1,89458, with a p-value of 0,003. Meanwhile, the Debt to Asset Ratio shows a negative and significant effect on Return On Assets, indicated by a t-value of  |-6,476|, which is lower than 1,89458, and a significance value of 0,000. Furthermore, the F-test shows that both variables together significantly influence Return On Asset, as reflected in an F-value of 27,728, which is greater than the critical F-table of 4,737, with a significance level of 0,000.